SURAT YASIN - Muhammad Muhyiddin Abdul Qodir (Universal Journal, 2023)
Surah Yasin is one of the central chapters of the Holy Qur'an that emphasizes the fundamental principles of Islamic faith, including the oneness of Allah (Tawhid), the truth of prophethood, divine revelation, accountability, and the reality of resurrection and the Hereafter. Through a qualitative library research approach, this study explores the theological, moral, and spiritual messages contained in Surah Yasin by examining its verses and interpretations from classical and contemporary Islamic scholarship. The analysis reveals that Surah Yasin provides comprehensive guidance for strengthening faith, encouraging reflection on the signs of Allah in creation, promoting righteous conduct, and preparing believers for eternal life. The chapter also highlights the consequences of accepting or rejecting divine guidance, illustrating the importance of obedience, gratitude, and perseverance in worship. Therefore, Surah Yasin serves not only as a source of spiritual inspiration but also as a practical framework for developing ethical values and a balanced life based on the teachings of the Qur'an.